Memahami Pendekatan keterampilan Proses dalam Pembelajaran Matematika - Nasution, Mariyam (IAIN PADANGSIDIMPUAN, 2014)
The approach is a basic concept that underlies a method of learning the theoretical coverage . Process approach is a teaching approach gives students the chance to participate live or a discovery process as a skill drafting process . Approach the learning process in mathematics known as process skills created by the teacher to the learning meaningful .. Teachers create varied forms of teaching activities that students are involved in a variety of situations . Skills in mathematics learning process aims to see : ability to observe , the ability to calculate , ability to measure , ability to classify , abilityÂ to find relationships , ability to make predictions ( forecast ) , ability to carry out research , ability to collect and analyze the data , ability to interpret the data , and ability to communicate the results.Â Based on the capabilities that will reach students and teachers must be able to work together in creating a learning environment that is conditioned in order skills in the process work as expected